2009
DOI: 10.1038/ja.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

Chemical biology of inflammatory cytokine signaling

Abstract: Pro-inflammatory cytokines, such as tumor necrosis factor-a and interleukin-1, trigger the signal transduction pathway leading to the activation of the transcription factor, nuclear factor-jB (NF-jB). NF-jB induces a large number of target genes involved in many biological processes, such as inflammation, immunity, cell survival, cell death and carcinogenesis. As therapeutic agents for inflammatory diseases and cancer, as well as bioprobes for the characterization of intracellular biological response and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 151 publications
3
29
0
Order By: Relevance
“…It is generally accepted that many intracellular signal pathways participate in the LPS-induced activation of macrophages and resultant production of pro-inflammatory cytokines/ mediators, and that nuclear factor NF -κB and mitogenactivated protein kinase MAPK pathways play key roles. NF-κB is one of the most ubiquitous transcription factors and coordinates the expression of pro-inflammatory enzymes and cytokines, making it a popular target for the development of potent inhibitors as novel anti-infl ammatory drugs [21][22][23][24] . Given the role of NF-κB in modulating the expression of infl ammatory mediators, it is possible that the inhibitory effects of D-limonene involve the inhibition of the NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that many intracellular signal pathways participate in the LPS-induced activation of macrophages and resultant production of pro-inflammatory cytokines/ mediators, and that nuclear factor NF -κB and mitogenactivated protein kinase MAPK pathways play key roles. NF-κB is one of the most ubiquitous transcription factors and coordinates the expression of pro-inflammatory enzymes and cytokines, making it a popular target for the development of potent inhibitors as novel anti-infl ammatory drugs [21][22][23][24] . Given the role of NF-κB in modulating the expression of infl ammatory mediators, it is possible that the inhibitory effects of D-limonene involve the inhibition of the NF-κB signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) We previously reported that (11S)-2α-bromo-3-oxoeudesmano-12,6α-lactone (1), initially designated as santonin-related compound 2 (SRC2; Fig. 1), inhibited cell-surface intercellular adhesion molecule-1 (ICAM-1) expression induced by interleukin-1β (IL-1β) in human lung carcinoma A549 cells.…”
Section: )mentioning
confidence: 99%
“…3) Sesquiterpene lactones are found in many plants, and have been attracting increasing attention for drug development due to their various biological activities, including anti-cancer and anti-inflammatory activities. 8,9) We previously reported that (11S)-2α-bromo-3-oxoeudesmano-12,6α-lactone (1), initially designated as santonin-related compound 2 (SRC2; Fig. 1), inhibited cell-surface intercellular adhesion molecule-1 (ICAM-1) expression induced by interleukin-1β (IL-1β) in human lung carcinoma A549 cells.…”
Section: )mentioning
confidence: 99%
“…Thus, it seems likely that the cardenolide aglycones act as translation inhibitors in the TNF-α-induced gene expression, except for those capable of inducing the ectodomain shedding of TNF receptor 1 and thereby blocking the TNF-α-induced NF-κB signaling pathway (e.g., glutarimides and triene-ansamycins). 39,40) Na + /K + -ATPase pumps Na + out and K + in via hydrolysis of ATP and plays a critical role in the maintenance of the Na + gradient across the plasma membrane. 41) The transport of amino acids across the plasma membrane is mediated by a broad range of transporters, including those coupling the influx of amino acids with the transmembrane gradient of Na + .…”
Section: Discussionmentioning
confidence: 99%